An Aspect of the Image of Power: The Portraits in the Cameos of Augustan Tradition - Fernández Uriel, Pilar (Eikón / Imago, 2013)
This article selects and classifies several cameos that are representative portraits of Augustus and male and female characters that belonged to the Julio-Claudian Gens. This involves a chronological period from 31 BC to 68 AD. Is a study with iconographic perspective, considering that their images convey a valuable historical documentation.